Infection Prevention And Control Of Dentistry Students In Tooth Extraction At Dental And Oral Hospital - Arti, Dwi Windu Kinanti; Talitha Olivia Sandra, Divi; Nurullita, Ulfa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Dental practice has risk becoming an entry point for infectious diseases in dental health facilities. Tooth extraction is an invasive procedure and it is necessary to do Infection Prevention and Control (IPC). The problems in implementation of IPC are not washing hands optimally, not using face shield, and the implementation of IPC in RSGM Unimus are not yet evaluated routinely. This research is descriptive study with cross sectional approach to describe the IPC behavior by dental students in tooth extraction at RSGM Unimus. Respondents in this study were 38 dental students at RSGM Unimus performed tooth extraction. The variables studied were age, gender, years of practice, habits in maintaining hand hygiene, use of PPE, handling of sharp objects, and safe injection practices. The sampling technique are accidental sampling. Most of the respondents were female, aged 24 years, and had practice period of 19-24 months. The ability to maintain hand hygiene is good for 36 respondents (94,7%), the use of PPE is good for 23 respondents (60,23%), handling sharp objects is good for 33 respondents (86,8%), and safe injection practices is good for 34 respondents (89,5%). In conclusion, IPC behavior by dental students at RSGM Unimus has been good.